MANAJEMEN RADIO UNTUK MENGELOLA PENDENGAR ANAK MUDA (Studi Deskriptif Kualitatif Mengenai Manajemen Penyiaran di Solo Radio) - Veronita, Monica; Ruthnia, Firdastin; Wiryawan, Hari (KOMUNITAS, 2013)
The objective of the research is to determine the radio management that applied for manageÂ theÂ youngÂ listenerÂ segmentationÂ inÂ soloradio.Â ThisÂ researchÂ belongÂ toÂ qualitative descriptiveÂ studyÂ thatÂ emphasizeÂ howÂ toÂ understandingÂ theÂ Â phenomenonÂ ofÂ theÂ experience with describe it into speech. TheÂ resultsÂ ofÂ thisÂ researchÂ isÂ broadcastingÂ managementÂ ofÂ soloradioÂ ofÂ soloradio usingÂ 4Â stagesÂ itÂ isÂ ,Â planning,Â organizing,Â actuatingÂ andÂ controlling.Â InÂ theÂ management, planning is good enough with the weekly meeting, monthly and yearly for planning programs thatâs compatible for young segmentation. Organizing is neatly supported by adequate human resources and the selection of the target youth broadcaster to be broadcast by both the sound according to the type of young people . Actuating done by providing guidance , motivation andÂ good relationsÂ with theÂ presentÂ approach to doingÂ good broadcasting programÂ andÂ in accordanceÂ withÂ theÂ youngÂ listenersÂ byÂ joiningÂ inÂ everyÂ eventÂ organizedÂ .Â AsÂ forÂ the controlling is done by a general manager who is directly and indirectly. But for the head of theÂ divisionÂ asÂ programÂ directorÂ toÂ superviseÂ directlyÂ dueÂ overseesÂ announcerÂ duringÂ the broadcast to keep it out of the path of a young.